Determination of energy-transfer distributions in ionizing ion-molecule collisions. Issue 15 (January 2020) - Indrajith, S; Erdmann, E; Chiarinelli, J; Domaracka, A; Łabuda, M; Avaldi, L; Alcami, M; Aguirre, N F; Díaz-Tendero, S; Bolognesi, P; Rousseau, P; Huber, B A
Synopsis: The main objective of this study is to determine the energy transfer occuring in ion-molecule collisions. In order to solve this problem, we followed two approaches; the first one by validating a purely experimental method and the second one by testing a new theoretical model M3 C (Microcanonical Metropolis Monte Carlo).